2018
DOI: 10.4103/ijo.ijo_1103_17
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between dry eye and refractive error in Saudi young adults using noninvasive Keratograph 4

Abstract: Purpose:The purpose is to study the correlation between dry eye and refractive errors in young adults using noninvasive Keratograph.Methods:In this cross sectional study, a total of 126 participants in the age range of 19–25 years and who were free of ocular surface disease, were recruited from King Saud University Campus. Refraction was defined by the spherical equivalent (SE) as the following: 49 emmetropic eyes (±0.50 SE), 48 myopic eyes (≤−0.75 SE and above), and 31 hyperopic eyes (>+0.75 SE). All particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
23
0
2
Order By: Relevance
“…These results are consistent with those previously reported. For example, the NITBUT readings obtained within a group of Saudi young females ( N = 126) were found to be significantly lower among subjects with myopia and hyperopia compared with those recorded in a normal eye group [ 30 ]. However, the TMH readings recorded among myopic and hyperopic subjects showed normal eye readings [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those previously reported. For example, the NITBUT readings obtained within a group of Saudi young females ( N = 126) were found to be significantly lower among subjects with myopia and hyperopia compared with those recorded in a normal eye group [ 30 ]. However, the TMH readings recorded among myopic and hyperopic subjects showed normal eye readings [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the NITBUT readings obtained within a group of Saudi young females ( N = 126) were found to be significantly lower among subjects with myopia and hyperopia compared with those recorded in a normal eye group [ 30 ]. However, the TMH readings recorded among myopic and hyperopic subjects showed normal eye readings [ 30 ]. The prevalence of dry eye among myopic, emmetropic, and hypermetropic subjects was 36.5, 24.6, and 17.4%, respectively [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study too, maximum cases with refractive error were found to be myopic (Spherical equivalent: -2.21±1.45D). 10 Prevalence of dry eye was also found to be more in myopic children in the study by Fahmy et al 16 Moon et al observed that an average of 5.46 hours was spent on smartphone and VDTs and a meagre 1.47 hours on outdoor activities in the affected group. Similar values were noted in the Category-A of the affected group in our study with an average of 5.33 hours spent on smartphones and VDTs and 1.32 hours spent outdoors.…”
Section: Djomentioning
confidence: 88%
“…50,70 Cyclosporine A for the Treatment of Surgically Induced Dry Eye Surgical intervention is sometimes required to address ophthalmic diseases. 6,13,61 Glaucoma, a major cause of blindness, is often treated with topical medications, but when medications are ineffective or contraindicated, surgery may be necessary. 13 Visually significant cataracts may also require surgical removal.…”
Section: Mechanism Of Action Of Cyclosporine Amentioning
confidence: 99%
“…3,4 Dry eye is commonly seen alongside many ocular disorders including glaucoma, cataracts, and refractive errors. [5][6][7] Pharmacological treatments for ocular disorders often contain preservatives such as benzalkonium chloride. 8 These preservatives can cause DED signs and symptoms including decreased epithelial cell integrity, increased epithelial cell apoptosis, eye irritation, and increased risk for ocular allergies and delayed hypersensitivity reactions.…”
Section: Introductionmentioning
confidence: 99%